Pengembangan Sistem Pengukuran Kinerja Program Kemitraan di PKBL PT Sucofindo, Jakarta - Arifin Derajat Suryana; Sapta Raharja; Amiruddin Saleh (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
The partnership program is a part of the activity  in the Partnership and Community  Development  Program  (PCDP)  as  a  form  of  responsibility  by revolving  funds  and  part  of  its  profits.  Up  to  now,  revolving  fund  of  the partnerships program has reached IDR 18.17 trillion and is growing every year, is need of good management and accurate performance measurement. Until now, the partnership program performance was measured by indicators of the effectiveness of distribution and level of collectibility loan repayment. There Indicators are still not able to describe the overall performance of the partnerships program,  which  may  cause  the  dysfunction  of  organization. Development  was  started  by identifying stakeholders’ expectations, then analyzing the methods of ranking, classification,   Logical   Framework Analysis (LFA), suitability analysis, Analytical Hierarchy Process (AHP), Focus Group Discussion  (FGD),  and Objective Matrix (OMAX). The analysis resulted in eight new indicators, which conducted the survey for the community stakeholders and small businesses with a sample of 30 respondents for each group of stakeholders, while for stakeholders’ employees, management, and state ministries was done census.  Respondents  selected  purposively.  The survey results show that the value of PCDP PT Sucofindo performance is 639.9, including a good performance status.